Case study on the implementation of inclusive education in certain private schools in Metro Manila - Mingoa, Thelma Rabago (Animo Repository, 2010)
Several laws recognize the necessity and urgency of providing education for children, youth and adults with special needs within regular schools. This study sought to find the existing state of inclusive education available to children with special education needs (SEN) in selected private schools in Metro Manila, and challenges in its implementation. Data collection from special and regular education teachers and students, parents and administrators revealed that each of the five private schools in the study had their own interpretation of what inclusive education is and how to implement it. Awareness and attitudes were different in all schools, specially among regular teachers who felt they need training. Services for children with SEN were insufficient or even non-existent. Recommendations include funding, training for teachers and administrators, home-school collaboration, linkages with community agencies and experts in the field, and further research on a nationwide scale.